Effect of salicylic acid on the transcript levels of SOD, POD and CAT in Nicotiana tabacum grown under Pb stress - Abdul Halim, Nurul Izzah; Phang, Ing Chia (2014)
Phytoremediation is a cost effective method which uses green plants to remediate Pb contaminants. Pb affects plant growth and development, and causes oxidative damage. Since plants are sessile organisms, compounds that can increase plant tolerance to Pb could enhance the efficiency of phytoremediation. In previous studies, SA was found to induce the level of antioxidant in plants, thus alleviating the harmful effect of excessive reactive oxygen species (ROS) level. It is likely that SA would reduce Pb-induced oxidative stress and increase the antioxidant capacity in Nicotiana tabacum. Superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) are antioxidative enzymes, which are commonly used as a marker for oxidative stress in plants. The present study aims to assess the effect of SA on the transcript levels of SOD, CAT and POD in N. tabacum grown under Pb treatments using a real time PCR. Firstly, N. tabacum was propagated and subjected to SA and Pb treatments. Then, RNA was isolated, cDNA was synthesized, and transcript levels of SOD, CAT and POD in N. tabacum were evaluated. The transcript levels of SOD, CAT and POD in SA pre-treated N. tabacum grown under Pb stress were compared to the controls and will be presented. The finding of this study improves our understanding on the effect of SA on the transcript level of SOD, CAT and POD in N. tabacum grown under Pb stress.